Hemin Improves Insulin Sensitivity in Skeletal Muscle in High Fat-Fed Mice - Tae-Jin Ju; Woo-Young Kwon; Yong-Woon Kim; Jong-Yeon Kim; Yong-Dae Kim; In-Kyu Lee; So-Young Park (Elsevier, 2014)
Abstract.: The present study examined whether hemin could prevent the development of high-fat diet-induced insulin resistance in the liver and skeletal muscle using a hyperinsulinemic-euglycemic clamp. A four-week high-fat feeding to mice increased the body weight, fat mass, and plasma levels of insulin and lipid, which were reduced by hemin. High-fat diet reduced whole body glucose uptake, which were increased by hemin. Insulin-stimulated hepatic glucose production (HGP) was increased by high-fat diet, but hemin had no significant effect on HGP. Skeletal muscle glucose uptake was reduced by high-fat diet, and hemin normalized the glucose uptake. High-fat diet increased triglyceride levels and mRNA levels of lipogenic enzymes, and decreased mRNA levels of enzymes involved in lipid β-oxidation, which was reversed by hemin. Phosphorylated AMP-activated protein kinase levels were increased in the skeletal muscle of high fat-fed hemin-injected mice. High-fat diet reduced mRNA levels of antioxidant enzymes and increased mRNA levels of inflammatory cytokines and nitrotyrosine levels, which was normalized by hemin in the skeletal muscle. However, hemin had no significant effect on these factors in the liver. These results suggest that hemin prevents the development of high-fat diet-induced insulin resistance by increased insulin sensitivity in the skeletal muscle. Keywords:: heme oxygenase-1, hemin, insulin resistance, high-fat diet, hyperinsulinemic euglycemic clamp